KESANTUNAN BERBAHASA MAHASISWA UNIKA WIDYA MANDALA MADIUN DALAM TUTURAN LANGSUNG - Wijayanti, Wenny (Widya Warta, 2020)
Language  has  function  as  acommunication  tool.  As  a  communication  tool,  there  are  several principles  that  need  to  be  considered  when  using  language.  In  college,  Bahasa  Indonesia becomes the compulsory course taken by the students. When using spoken language, students are likely to choose the incorrect words, do not know the situation when they communicate, and do not know the social status with the interlocutors. Based on these situations, the study aims to describe the form of compliance and the violation of the language use in the afternoon class and morning class. This research was a qualitative descriptive study with the data were in the form of students’ direct speech and the source of data was derived from the students taking the general course of Bahasa Indonesia. From the results of the research, it is  known that there are the  compliances  and  violations  of  the  politeness  principles.  The  compliances  of  politeness principles in the afternoon class were the compliances to the maxim of the agreement, tact, and approbation,  while  the  compliances  of  politeness  principles  in  the  morning  class  were  the compliances  to  the  maxim  of  agreement,  tact,  and  sympathy.  The  violations  of  politeness principles conducted by the students in the afternoon class were the violations to the maxim of approbation, sympathy, and tact, while the violations of politeness principles conducted by the students  in  the  morning  class  were  the  violations  to  the  maxim  of  tact,  modesty,  and approbation.